2000
DOI: 10.1021/jf9908493
|View full text |Cite
|
Sign up to set email alerts
|

Unsaponifiable Lipid Constituents of Some Underutilized Tropical Seed Oils

Abstract: Sterols, triterpene alcohols, and hydrocarbons present in the unsaponifiable fraction of some underutilized tropical seed oils have been examined. The seeds include Telfairia occidentalis (TLO), Andenopus breviflorus (ADB), Cucumeropsis edulis (CME), Antiaris africana (ATF), and Monodora tenuifolia (MNT). The oil content of the seeds was high (34.7-68.8%), whereas triacylglycerols comprised the dominant lipid group in the oils (65.4-73.9%). The percentage of unsaponifiables ranged from 1.1 to 7.9%. Ten sterols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…Although the fruits are reported to be edible and the seeds used as an antidysenteric 1, there has been no other documented uses. Available literature on the seed is scanty; however, the fatty acid composition of the seed oil has been reported 2. There is no data available on the seed productivity of A. africana tree at present possibly because the seeds have not found any industrial use.…”
Section: Introductionmentioning
confidence: 99%
“…Although the fruits are reported to be edible and the seeds used as an antidysenteric 1, there has been no other documented uses. Available literature on the seed is scanty; however, the fatty acid composition of the seed oil has been reported 2. There is no data available on the seed productivity of A. africana tree at present possibly because the seeds have not found any industrial use.…”
Section: Introductionmentioning
confidence: 99%
“…However, GC-MS reports on the constituents of the seed oils did not identify any of the alkaloids inferred from the LC-MS results (Tables S3 and S4). The major compounds identified under GC-MS were terpenes, fatty acids and triglycerols (Esuoso et al, 2000). The compounds identified under LC-MS in this study were mostly non-volatile and could not have been identified by GC-MS.…”
Section: Resultsmentioning
confidence: 61%
“…Previous phytochemical reports on the constituents of the seed oils of these plant materials were by GC-MS (Esuoso et al, 2000, Adewole et al, 2013. However, GC-MS reports on the constituents of the seed oils did not identify any of the alkaloids inferred from the LC-MS results (Tables S3 and S4).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to a stearic and oleic acids rich saponifiable fraction, Shea butter contains an unsaponifiable fraction composed of bioactive substances that are responsible for Shea butter's medicinal properties [32]. With regional variation in concentrations [6,33], the unsaponifiable fraction of Shea butter is composed primarily of triterpene alcohols, with some hydrocarbons, sterols, and other minor components such as vitamin E [34][35][36].…”
Section: Chemical Composition Of Shea Buttermentioning
confidence: 99%
“…Collagen and elastin are the major structural proteins providing skin with toughness and plumpness and α-amyrin and lupeol, the triterpenes found in the unsaponifiable fraction of Shea butter, were found to contribute to the inactivation of proteases such as metalloprotease (e.g., collagenase) as well as serine protease (e.g., elastase) [36]. The anti-aging, potentially collagen-boosting effects were attributed to its unsaponifiable components [32,36].…”
Section: Effects Of Shea Buttermentioning
confidence: 99%